Level of knowledge about basal cell carcinoma in Stomatology students - Annalie Elizabeth Frías Pérez; Elizabeth Vázquez Blanco; Milagros de la Caridad Pérez Suárez; Lisandra Vázquez Carvajal; César Ramón Góngora Ávila; Yanisel Josefina Zayas Vázquez (Universidad de Ciencias Médicas de Granma, 2022)
Introduction: basal cell carcinoma is the most diagnosed skin cancer, which requires an adequate knowledge of its diagnosis, characteristics and treatment by the stomatologist given the incidence of patients with this pathology. Objective: to determine the level of knowledge of the Stomatology students of the Faculty of Medical Sciences of Manzanillo about basal cell carcinoma. Method: a descriptive, cross-sectional study was carried out in Stomatology students from the Faculty of Medical Sciences of Manzanillo, from April to May 2021. The universe consisted of 80 students belonging to the fourth and fifth year of Stomatology. A survey was made in Google Forms, where the variables referring to the level of knowledge of the students about basal cell carcinoma were studied. The level of knowledge was evaluated as good, regular and bad and for information processing a database was created in SPSS and Cronbach's alpha coefficient and Fisher's exact test were determined. Results: fifth-year Stomatology students predominated (82,5 %), a predominance of the level of regular knowledge in terms of epidemiology, anatomical location and treatment of basal cell carcinoma (48,75 %, 52,5 % and 56,25 % respectively) was observed and a good level of knowledge about the etiology of basal cell carcinoma (53,75 %) and 63,75 % of the students reported the need for a study on basal cell carcinoma. Conclusions: the level of knowledge it was Regular in most of the variables evaluated about the knowledge of basal cell carcinoma.